LncRNA MEG3 Reduces the Ratio of M2/M1 Macrophages Through the HuR/CCL5 Axis in Hepatocellular Carcinoma - Wei H; Wu X; Huang L; Long C; Lu Q; Huang Z; Huang Y; Li W; Pu J (Journal of Hepatocellular Carcinoma, 2024)
Huamei Wei,1,* Xianjian Wu,2,* Lizheng Huang,3,* Chen Long,3 Qi Lu,3 Zheng Huang,3 Yanyan Huang,3 Wenchuan Li,2 Jian Pu2 1Department of Pathology, Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi, People’s Republic of China; 2Department of Hepatobiliary Surgery, Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi, People’s Republic of China; 3Graduate College of Youjiang Medical University for Nationalities, Baise, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Pu, Affiliated Hospital of Youjiang Medical University for Nationalities, No. 18 Zhongshan Two Road, Baise, Guangxi, 533000, People’s Republic of China, Email Pujianym@163.comObjective: Tumor-associated macrophages play a crucial role in the development of hepatocellular carcinoma (HCC). Our study aimed to investigate the relationship between long coding RNA (lncRNA) maternally expressed gene 3 (MEG3), RNA-binding protein human antigen R (HuR), and messenger RNA C–C motif chemokine 5 (CCL5) in the modulation of M1 and M2 macrophage polarization in HCC.Methods: To induce M1 or M2 polarization, LPS/IFNγ- or IL4/IL13 were used to treat bone marrow derived macrophages (BMDMs). The localization of MEG3 in M1 and M2 macrophages was assessed using fluorescence in situ hybridization assay. Expression levels of MEG3, HuR, CCL5, M1, and M2 markers were measured by RT-qPCR or immunofluorescence staining. Flow cytometry was performed to determine the proportion of F4/80+CD206+ and F4/80+CD68+ cells. RNA pulldown assay was performed to detect the binding of lncRNA MEG3 and HuR. The impacts of HuR on CCL5 stability and activity of CCL5 promoter were evaluated using actinomycin D treatment and luciferase reporter assay. Cell migration, invasiveness, and angiogenesis were assessed using transwell migration and invasion assays and a tube formation assay. A mixture of Huh-7 cells and macrophages were injected into nude mice to explore the effect of MEG3 on tumorigenesis.Results: MEG3 promoted M1-like polarization while dampening M2-like polarization of BMDMs. MEG3 bound to HuR in M1 and M2 macrophages. HuR downregulated CCL5 by inhibiting CCL5 transcription in macrophages. In addition, overexpression of MEG3 suppressed cell metastasis, invasion, and angiogenesis by obstructing macrophage M2 polarization. MEG3 inhibited tumorigenesis in HCC via promotion of M1-like polarization and inhibition of M2-like polarization. Rescue experiments showed that depletion of CCL5 in M2 macrophages reversed MEG3-induced suppressive effect on cell migration, invasion, and tube formation.Conclusion: MEG3 suppresses HCC progression by promoting M1-like while inhibiting M2-like macrophage polarization via binding to HuR and thus upregulating CCL5.Keywords: hepatocellular carcinoma, maternally expressed gene 3, macrophage polarization, human antigen R, C-C motif chemokine 5